2004
DOI: 10.1016/j.ultsonch.2003.07.004
|View full text |Cite
|
Sign up to set email alerts
|

High power ultrasound effects on lipid oxidation of refined sunflower oil

Abstract: The effects of high power ultrasound treatment (20 kHz) on some components of refined sunflower oil were studied in order to verify if and to what extent modifications in the lipidic fraction can occur. Traditional parameters including free acidity, total polar compounds, peroxide value, and conjugated dienes concentration were determined in refined sunflower oil samples before, immediately after the ultrasonic treatment and during storage. Differences between treated and untreated samples were detected only f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(80 citation statements)
references
References 9 publications
5
68
0
3
Order By: Relevance
“…These off flavour may be due to the oxidation of fatty acid present in the product. Chemat et al, 2004 verified oxidation in oil emulsions after sonication even when in indirect contact with the ultrasound source.…”
Section: Effect Of Ultrasonic Assisted Extraction On Fatty Acid Profimentioning
confidence: 76%
See 1 more Smart Citation
“…These off flavour may be due to the oxidation of fatty acid present in the product. Chemat et al, 2004 verified oxidation in oil emulsions after sonication even when in indirect contact with the ultrasound source.…”
Section: Effect Of Ultrasonic Assisted Extraction On Fatty Acid Profimentioning
confidence: 76%
“…The recent studies have shown that the ultrasound-assisted extraction of can enhance the extraction efficiency through acoustic cavitation and some mechanical effects (Chemat et al, 2012(Chemat et al, , 2004Rostagno et al, 2003). Acoustic cavitation can disrupt cell walls facilitating solvent to penetrate into the plant material and allowing the intracellular product release.…”
Section: Introductionmentioning
confidence: 99%
“…However, effect of starter culture on fatty acid profile of beef jerky has not been reported to date. Additionally, ultrasound assisted extraction has shown to influence the fatty acid profile of oils depending on the food matrix and extraction conditions (Chemat et al, 2004a;Xu et al). To date no study reports the effect of high power ultrasound on fatty acid profile of meat and/or fermented meat products.…”
Section: Introductionmentioning
confidence: 99%
“…The increased PV of oils after ultrasonic processing may be caused by heating or exposure to active species, e.g., active hydrogen atom (H + ) due to ultrasonic-induced pyrolyzation of water molecules. Chemat et al 11 reported an almost 20% increase of PV in a refined sunflower oil when processed by high power ultrasound; meanwhile, many off-flavour compounds were released due to the oil oxidation. The possible mechanism is as follows: upon formation of sufficient free radicals, the chain reaction on both PUFAs and MUFAs was initiated by the abstraction of H + adjacent to the double bonds and subsequently attacked at these locations resulting in the production of peroxy radicals.…”
Section: Analysis Of Raw Oils and Oil Phasementioning
confidence: 99%
“…Lipid degradation and oxidation have been reported to be accelerated with the introduction of ultrasound. Chemat et al 11 studied the sono-degradation of sunflower oil and found that off-flavour compounds, e.g., limonene and hexanal, were released after sonication of 2 min at 20 kHz of frequency and 150 W of power. Another study focusing on the sono-oxidation of sunflower oil also reported a significant increase in peroxide value (PV) and a decrease in the concentration of unsaturated fatty acids after 30 min of ultrasonic treatment (f = 20 kHz and P = 150 W).…”
Section: Introductionmentioning
confidence: 99%